(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
This essay explores what it means to be human, connecting challenging conceptual ideas to my recent experience in 5k. It delves into humans’ distinct emotional complexity and empathy, arguing how these traits distinguish us from other life and artificial intelligence. I intertwine my personal story with texts from class and my own reasoning to try to grasp what is at the center of our shared humanity. For additional context, listen to the author’s reflection on the piece below.